Immunoglobulin G subtypes‐1 and 2 differentiate immunoglobulin G4‐associated sclerosing cholangitis from primary sclerosing cholangitis. Issue 5 (1st June 2020) - Vujasinovic, Miroslav; Maier, Pia; Maetzel, Hartwig; Valente, Roberto; Pozzi‐Mucelli, Raffaella; Moro, Carlos F; Haas, Stephan L; Said, Karouk; Verbeke, Caroline S; Maisonneuve, Patrick; Löhr, J‐Matthias
Abstract : Background: Autoimmune pancreatitis is a special form of chronic pancreatitis with strong lymphocytic infiltration and two histopathological distinct subtypes, a lymphoplasmacytic sclerosing pancreatitis and idiopathic duct centric pancreatitis. Immunoglobulin G4‐associated cholangitis may be present at the time of autoimmune pancreatitis type 1 diagnosis or occur later over the course of the disease. Immunoglobulin G4 is considered reliable but not an ideal marker for diagnosis of autoimmune pancreatitis type 1 with reported sensitivity between 71–81%. It is essential to differentiate sclerosing cholangitis with autoimmune pancreatitis from primary sclerosing cholangitis as the treatment and prognosis of the two diseases are totally different. It was the aim of the study to find a marker for immunoglobulin G4‐associated cholangitis that would distinguish it from primary sclerosing cholangitis. Patients and methods: We performed a retrospective analysis of patients with autoimmune pancreatitis at our outpatient clinic. Patients from the primary sclerosing cholangitis registry were taken as a control group. Blood samples for the measurement of immunoglobulin subclasses were analysed at the time of diagnosis. Results: Patients with autoimmune pancreatitis and immunoglobulin G4‐associated cholangitis had higher values of immunoglobulin G2 when compared to autoimmune pancreatitis alone or primary sclerosing cholangitis with a high specificity (97%) and high positive predictive value (91%). In patients with normal or low immunoglobulin G2 or immunoglobulin G4, a high level of immunoglobulin G1 indicated primary sclerosing cholangitis. Conclusion: Immunoglobulin G1 and immunoglobulin G2 can distinguish patients with immunoglobulin G4‐associated cholangitis from those with primary sclerosing cholangitis.